EXPLORATION OF THE POTENTIAL OF BLOCKCHAIN TECHNOLOGY IN SECURING DATA AND EDUCATIONAL CREDENTIALS - Azahra, Suci Rizkiah (Educational Technology Journal, 2024)
Blockchain technology has emerged as a potential solution for ensuring data security and integrity in various fields, including education. In this publication, we explore the potential of blockchain technology in securing educational data and credentials. We start by providing an introduction to the basic concepts and principles of blockchain technology. Next, we explain how blockchain technology can be used to create a secure and trusted system for storing educational data, including academic history, certificates, and transcripts. We also discuss the use of blockchain in securing educational credentials, such as degrees and certificates, as well as concepts such as credential tokenization and decentralized verification. We identified possible advantages to be gained from the application of blockchain technology in education, including increased security, transparency, and reduced administrative costs. However, we also acknowledge challenges, such as scalability, privacy, and legal and regulatory barriers. Through case studies and existing implementation projects, we provide real-life examples of how blockchain technology has been tested and applied in educational contexts. In conclusion, blockchain technology has great potential for securing data and educational credentials. In an educational context, blockchain can improve security, transparency, and efficiency. However, challenges and barriers need to be overcome for the application of blockchain in education to become more widespread and successful.